Mapping Practices and Technologies of Climate-Smart Agriculture in Bangladesh - Mahashin, M; Roy, R (Journal of Environmental Science and Natural Resources, 2018)
Climate-Smart Agriculture (CSA) is an integrative approach of increasing productivity, enhancing resilience, and minimizing greenhouse gas emissions. The study addresses four research questions: (I) How many agro-region based climate change hot spots are there in Bangladesh with specific reference to CSA, (II) what are the contribution of practices and technologies of CSA? (III) How institutional involvement promoting CSA practices and technologies? A mixed method, i.e. literature review, discussion with experts, gathering information from the DAE, was employed to carry out the study. Results indicate that farmers have been practicing CSA at a smaller-scale and investment on knowledge, learning and capacity development is a key means for a full-scale CSA implementation. Findings illustrate that broad types of practices and technologies have been addressing three intertwined challenges: ensuring food security, impacts of climate change on agriculture and agriculture’s impact on climate change. The government’s project-based endeavor of implementing CSA marks that they have been pledged to defeat the climatic risks in agriculture. Active initiative for mainstreaming CSA into national policies and programs are inadequate. J. Environ. Sci. & Natural Resources, 10(2): 29-37 2017